Information and Software Technologies 20th International Conference, ICIST 2014, Druskininkai, Lithuania, October 9-10, 2014, Proceedings - Dregvaite, Giedre.; Dregvaite, Giedre.; Damasevicius, Robertas.; Damasevicius, Robertas. (Communications in Computer and Information Science,, 2014)
This book constitutes the refereed proceedings of the 20th International Conference on Information and Software Technologies, ICIST 2014, held in Druskininkai, Lithuania, in October 2014. The 34 papers presented were carefully reviewed and selected from 68 submissions. The papers are organized in topical sections such as information systems; business intelligence for information and software systems; software engineering; information technology applications.